2021
DOI: 10.1093/jamia/ocab038
|View full text |Cite
|
Sign up to set email alerts
|

CancelRx: a health IT tool to reduce medication discrepancies in the outpatient setting

Abstract: Objective Medication list discrepancies between outpatient clinics and pharmacies can lead to medication errors. Within the last decade, a new health information technology (IT), CancelRx, emerged to send a medication cancellation message from the clinic’s electronic health record (EHR) to the outpatient pharmacy’s software. The objective of this study was to measure the impact of CancelRx on reducing medication discrepancies between the EHR and pharmacy dispensing software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Although there has been research to demonstrate how CancelRx affects health system outcomes, such as reducing medication list discrepancies, little is known about how this novel health IT affected the medication discontinuation workflow for pharmacy staff and how these processes changed over time after implementation. 3 , 4 …”
Section: Cancelrxmentioning
confidence: 99%
“…Although there has been research to demonstrate how CancelRx affects health system outcomes, such as reducing medication list discrepancies, little is known about how this novel health IT affected the medication discontinuation workflow for pharmacy staff and how these processes changed over time after implementation. 3 , 4 …”
Section: Cancelrxmentioning
confidence: 99%
“…However, in 2017, Surescripts removed these financial restraints, which helped with some adoption. 5 CancelRx also experienced a "chicken-and-egg" syndrome in which many pharmacies declined to activate the functionality because there were not many prescribers sending CancelRx messages. Many prescriber organizations in turn would not activate the Can-celRx functionality because there were not many pharmacies able to receive their CancelRx messages.…”
Section: Slow Adoption Of Cancelrxmentioning
confidence: 99%
“…6 Although not frequently published, several organizations have successfully used CancelRx, such as the University of Wisconsin-Madison and Johns Hopkins Health System. 5,7…”
Section: Not Necessarily a Technical Challengementioning
confidence: 99%
“…In a pilot study, Pitts et al demonstrated that CancelRx functionality successfully discontinued medications in the pharmacy’s dispensing software that had been discontinued in the prescriber’s EHR 92.4% of the time [ 23 ]. Similarly, a study by Chui et al, showcased not only a 93% success rate for CancelRx communication medication discontinuations, but also a drastic reduction in the amount of time required for a medication to be discontinued in the pharmacy software after it was discontinued at the clinic [ 24 ].…”
Section: Introductionmentioning
confidence: 99%